Cell-cell communication-mediated cell-type-specific parent-of-origin effects in mammals - Jia-Jin Wu; Enqin Zheng; Langqing Liu; Jianping Quan; Donglin Ruan; Zekai Yao; Jifei Yang; Xuehua Li; Shiyuan Wang; Ming Yang; Zebin Zhang; Meng Lin; et al. (Nature Communications)
Abstract Genomic imprinting is manifested as monoallelic expression of genes according to parental origin, which is closely linked to mammalian placentation and human diseases. Yet, it is unclear how genomic imprinting evolves in different cell types. Here we generate a single-nucleus transcriptomic landscape of mammalian placental development, identifying 5 major cell types and 14 trophoblast subtypes. By developing a framework for integrating the datasets of single-nucleus transcriptome and whole-genome variations from reciprocal crosses of the genetically distinct Duroc and Lulai pig breeds, we construct a cell-type-specific genomic imprinting landscape, uncovering 118 candidate imprinted genes. We expand the mammalian imprinting gene catalog by identifying 97 previously uncharacterized imprinted candidates. Nearly 75% of imprinted candidates exhibit a cell-type- and developmental-stage-dependent manner. Through cross-species analysis, we show that cell-cell communication, especially the integration and modification of signaling pathways into a cell-type-specific autocrine network, drives biased allelic expression of imprinted genes in pigs, mice, and humans. Our findings provide genetic and molecular insights into parent-of-origin effects on gene expression, offering an in-depth understanding of genomic imprinting in mammals.